Modification Of High-Protein Healthy PMT (Supplementary Feeding) As An Effort To Prevent Stunting And Malnutrition In Nagari Kamang Hilia, Kamang Mudiak District, Agam - Melindra Mulia; Elsa Yuniarti; Desy Kurniawati; Della Rosalyna Stiadi; Fauzana Gazali; Fitri Yuranda; Raisya Pratama Putri; Nadila Safitri (Pelita Eksakta, 2025)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake over a long period of time, resulting in impaired optimal physical and cognitive development. The problem of stunting and malnutrition requires coordination between various parties to overcome it. In Agam Regency, especially Nagari Kamang Hilia, the stunting rate is still relatively high, with a prevalence of 24.6%, according to the latest Indonesian Nutrition Status Survey (SSGI). One of the factors influencing this is the high cost of nutritious food, which reduces the interest of mothers in serving healthy menus for the family. Therefore, education and training on nutritious food processing with alternative food sources is needed to increase public understanding. This program targets posyandu cadres and PKK mothers as the main targets, with the aim of providing knowledge about the importance of fulfilling nutrition to prevent stunting and malnutrition. The results of this activity are expected to increase awareness and interest of mothers in processing nutritious food that is attractive and liked by families, especially children.